The karate kid II [videorecording (DVD)] : the story continues - Avildsen, John G., 1935-2017; Macchio, Ralph, 1961-; Morita, Pat, 1932-2005 (Sony Pictures Home Entertainment, 2005)
Karate student Daniel LaRusso (Macchio) accompanies his teacher, Miyagi, (Morita) to Miyagi's ancestral home in Okinawa and becomes involved in a collision of cultures and combat.